SERVICE CO-CREATION AND CUSTOMER WELL-BEING: THE MEDIATING ROLE OF CUSTOMER ENGAGEMENT - santi santi; Roberto Tomahuw (Journal Civics And Social Studies, 2026)
The coffee shop industry in Tangerang is experiencing rapid growth as people's lifestyles evolve, making coffee shops not only places to enjoy beverages but also social spaces, work environments, and interaction hubs. In this context, companies are required to create service experiences that actively involve customers thru service co-creation. This study aims to analyze the influence of service co-creation on customer well-being with customer engagement as a mediating variable among Starbucks Coffee Tangerang customers. The research uses a quantitative approach with a survey method involving 135 respondents who are customers of Starbucks Coffee Tangerang and have made at least two purchases in the last six months. The sample size was determined using a non-probability sampling technique with a purposive sampling method, which met the SEM-PLS analysis requirements. The research instrument was a questionnaire with a five-point Likert scale that had been tested for validity and reliability thru outer model testing, while data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with stages of measurement model evaluation (convergent validity, discriminant validity, and construct reliability) and structural model (R² value, path coefficient, effect size (f²), and significance test thru bootstrapping procedure). The research results show that service co-creation has a positive and significant effect on customer engagement (β = 0.693; p < 0.000) and customer well-being (β = 0.672; p < 0.001). Additionally, customer engagement positively affects customer well-being (β = 0.696; p < 0.000) and can partially mediate the relationship between service co-creation and customer well-being. The coefficient of determination (R²) value of 0.45 for the customer engagement variable indicates that 45% of the variation in customer engagement can be explained by service co-creation, while the R² value of 0.75 for customer well-being indicates that 75% of the variation in customer well-being is explained by the combination of service co-creation and customer engagement. These findings contribute to the development of service marketing literature, particularly from the perspective of Service-Dominant Logic, and provide input for Starbucks Coffee Tangerang in enhancing customer experience thru value co-creation.